Water balance during and after marathon running - Pastene, J.; Germain, M.; Allevard, A. M.; Gharib, C.; Lacour, J. R. (European Journal of Applied Physiology, 1996)
To describe the time course of plasma volume alterations and the changes in the plasma concentrations of hormones regulating water balance in relation to a marathon race, six experienced marathon runners (five men, one women) aged 28 (SD 6) years were studied during and for the 3 days following a treadmill marathon run at 68 (SD 5) percent of maximal oxygen consumption. Haematocrit, haemoglobin, plasma protein (Prot) and electrolyte (Na+, K+) concentration, osmolality (osm), plasma concentrations of renin (Ren), aldosterone (Ald) and atrial natriuretic peptide (ANP) were determined at rest in a sitting position (T(-30)), and then after 30 min in an upright posture (R(0)), while running a marathon at 10 km (R(10)), 30 km (R(30)) and 42.2 km (R end), and after the marathon at 30 min (T(30)), 60 min (T(60)), 120 min (T(120)) and 24 h (TD(+1)), 48 h (TD(+2)) and 72 h (TD(+3)). The changes in plasma volume (PV), Prot, osm and Na+ observed during the race were nonsignificant. Significant increases in plasma concentration of K+ [4.8 (SD 0.6) vs 5.5 (SD 0.6) mmol*1(-1); P <0.01], Ren [38(SD 57) vs 197 (SD 145) pmol*1(-1); P <0.02] and Ald [175 (SD 142) vs 1632 (SD 490) pmol*1(-1); P <0.01] were observed at R(end). A significant increase of ANP (P <0.05) was only found after R(10). Body mass significantly decreased by 2.0 kg (P <0.01) during the race in spite of the ingestion of 1.46 (SD 0.34)1 of a 5 percent glucose solution. Urinary volume and Na+ excretion dropped significantly after the completion of the marathon in comparison with the day before [2600 vs 1452 ml*day(-1)(P <0.02) and 161.3 vs 97.1 mmol*1(-1) (P <0.05)]. At TD(+1) and TD(+2) a significant increase in PV was noted, compared to T(-30). The lack of a decrease in PV during the marathon may have been due to the production of 402 g of metabolic water and by the release of 1280 g of water stored in glycogen complexes in muscle and liver. Thus, the hormone response during the marathon may have been due to the effects of the exercise itself and not to the effects of dehydration. The postmarathon PV expansion may be explained by a protein shift to the intravascular space and by renal sodium retention.